2022
DOI: 10.1186/s12877-022-02869-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association of obesity-related measures with multi-morbidity among older adults in India: evidence from LASI, Wave-1

Abstract: Background Co-existence of multiple chronic diseases is increasingly becoming a norm among ageing population. The study aims to investigate the prevalence of multimorbidity and the association between anthropometric measures of obesity and multimorbidity among men and women aged 60 years and above in India. Methods The present study is based on the first wave of the Longitudinal Aging Study in India. The analytical sample size for the study was 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Hence, the successful aging disparity can partially be explained by the differential poverty and illiteracy rates in urban and rural areas. Also, as evidence suggests, older people with higher socioeconomic status and those who reside in urban areas are more likely to have several lifestyle diseases including obesity [ 22 , 68 , 69 ] which may ultimately result in poor mental and physical performance and lower rate of successful aging.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the successful aging disparity can partially be explained by the differential poverty and illiteracy rates in urban and rural areas. Also, as evidence suggests, older people with higher socioeconomic status and those who reside in urban areas are more likely to have several lifestyle diseases including obesity [ 22 , 68 , 69 ] which may ultimately result in poor mental and physical performance and lower rate of successful aging.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with our findings, which showed that there were more girls than boys who were overweight and indicated that boys have a lower risk of being overweight than girls. This situation can be seen in the adult population as well, with women having the greatest likelihood of being overweight [ 23 , 24 ]. A study by Zong and his colleagues found that children raised in an extended family, mainly raised by their grandparents, or in high-income households may have an increased risk of becoming obese/overweight [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…| 3 of 20 included in this systematic review. 1,18,19,[50][51][52][53][54][55][56][57][58][59][60][61][62] Out of these 16 studies, 15 were included in the meta-analysis. 1,18,19,50,[52][53][54][55][56][57][58][59][60][61][62] Figure 1 shows the process of study selection and inclusion.…”
Section: Inclusion Of Studiesmentioning
confidence: 99%